Traumatic meningeal enhancement detection by deep learning-based biomedical image analysis and handcrafted features extraction - Uddin, Mohammad Sakib; Nidhi, Nusrat Jahan; Yesmin, Sadia; Roy, Proloy Kanti (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.